Risk assessment of incontinence-related dermatitis in critically ill patients and analysis of related graded nursing measures (危重症患者发生失禁相关性皮炎的风险及相关分级护理措施分析) - ZHUANG Haiyan (庄海燕); ZHANG Yuanyuan (张媛媛); XIONG Meifeng (熊梅凤) (Association of Integrative Nursing, 2022)
Objective To study and analyze the risk assessment and graded nursing measures of incontinence-related dermatitis (IAD) in critically ill patients. Methods From February 2017 to February 2020, 80 critically ill patients with fecal and/or urinal incontinence who received treatment in hospital ICU were included in this study. The patients were divided into observation group and control group according to computer random number table method, with 40 cases in each group. The control group received routine skin care, and the observation group received IAD risk assessment and graded nursing intervention on the basis of the control group. The differences in the occurrence of IAD, rehabilitation, psychological status and complications between the two groups were analyzed. In addition, the difference between the two groups in the changes of self-esteem was analyzed. Results The total incidence of IAD in observation group was significantly lower than that of the control group (P < 0. 05). The healing time of skin lesions in the observation group was shorter than that in the control group, and the recurrence rate after healing was lower than that in the control group (P < 0. 05). After intervention, the positive emotional score of the observation group was higher than that of the control group, while the negative emotional score of the observation group was lower than that of the control group (P < 0. 05). The total incidence of complications in observation group was lower than control group (P < 0. 05). The Rosenberg self-esteem scale(RSES) scores of the observation group and the control group were increased after intervention, and scores in the observation group were higher than those in the control group (P < 0. 05). Conclusion Risk assessment and graded nursing of IAD in critically ill patients can reduce the risk of IAD to a certain extent, promote the early recovery of patients, and effectively reduce the incidence of complications. (目的 研究危重症患者发生失禁相关性皮炎(IAD)的风险评价与分级护理措施。方法 选取2017年2月-2020年2月在医院ICU接受诊治的80例大便或(和)小便失禁危重症患者纳入研究。按照随机数字表法分作观察组和对照组, 各40例。对照组开展常规皮肤护理, 观察组则于对照组的基础上采用IAD的风险评价与分级护理措施干预。分析两组IAD发生情况、康复情况、心理状况以及并发症发生情况的差异。此外, 分析两组自尊水平变化情况的差异。结果 观察组IAD总发生率低于对照组(P＜0. 05)。观察组皮损愈合时长短于对照组, 且治愈后复发率低于对照组, 差异有统计学意义(P＜0. 05)。观察组干预后正性情绪评分高于对照组, 而负性情绪评分低于对照组, 差异有统计学意义(P＜0. 05)。观察组并发症总发生率低于对照组(P＜0. 05)。观察组与对照组干预后Rosenberg自尊量表(RSES)评分高于干预前, 且观察组高于对照组(P＜0. 05)。结论 危重症患者IAD的风险评价与分级护理可在一定程度上降低IAD发生风险, 同时促进患者的早日康复, 并有效降低并发症发生风险。)